YumScore Sentiment-Driven Restaurant Recommendation System - AHMAD ZAIDI, AHMAD SYAWAL; ABDUL JALIL, ROZITA (Applied Information Technology And Computer Science, 2025)
In Johor, Malaysia, where culinary choices are abundant, selecting the ideal restaurant can be an overwhelming endeavor. This study addresses this challenge by developing YumScore, an advanced restaurant recommendation system utilizing sentiment analysis. By employing sophisticated sentiment analysis models such as RoBERTa and VADER, YumScore analyzes online reviews to provide unbiased and accurate restaurant ratings. Developed through an iterative prototyping approach with a focus on user-centered design, YumScore aims to deliver personalized dining recommendations that align with individual preferences. This system not only enhances customer satisfaction by helping users make informed dining choices but also offers valuable insights to restaurant owners, facilitating informed decision-making and promoting economic growth. YumScore has the potential to transform dining experiences in Parit Raja, Johor, leveraging cutting-edge technology to support the city’s vibrant culinary landscape.